2013
DOI: 10.1016/j.molonc.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Targeted serum miRNA (TSmiR) test for diagnosis and follow‐up of (testicular) germ cell cancer patients: A proof of principle

Abstract: Germ cell cancers (GCC) are the most frequent malignancy in young Caucasian males. GCC can consist of seminomas (SE) and non-seminomas (malignant NS: embryonal carcinoma (EC), yolk sac tumor (YS), choriocarcinoma (CH) and teratoma (TE)). Current serum-markers used for diagnosis and follow-up (AFP, hCG) are predominantly related to YS and CH and marker positivity can vary during disease. Therefore, stable markers consistently identifying more GCC components, specifically the stem cell components SE and EC, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(146 citation statements)
references
References 32 publications
4
134
0
8
Order By: Relevance
“…Once the source of production is eliminated, serum levels are supposed to clear. Similar results have been reported previously [15,16,24], and the present report is a confirmation based on a larger patient number.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Once the source of production is eliminated, serum levels are supposed to clear. Similar results have been reported previously [15,16,24], and the present report is a confirmation based on a larger patient number.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, microRNAs (miRs) have been suggested to be a novel class of serum biomarkers [10,11,12]. Regarding testicular GCT, miRs-371-3 as well as miR-302 and miR-367 represent promising candidates [13,14,15,16,17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tests targeting these specific miRNAs are currently under development. Preliminary studies have already proven great specificity (99-100%) and sensitivity of these tests for the detection of TGCT [100][101][102]. Other body fluids are also suitable for detection of miRNA released by disseminated tumours, e.g.…”
Section: Traces Of Gct In Blood: Classical Biochemical Markers and MImentioning
confidence: 99%
“…5 Patients in clinical stage I also showed a decline of circulating miRNAs following orchidectomy. Further research in a series with 80 TGCT patients confirmed the excellent sensitivity of serum miRNAs: 8 an increase of miR-371, miR-372, miR-373, or miR-367 was observed in 98% of the examined TGCT patients; the miRNAs thus outperformed AFP (36%) and HCG (57%). Our own data also confirm the improved sensitivity (85%) and specificity (99%) of miR-371 when compared to AFP (14%) and HCG (37%).…”
Section: Nucleic Acids Micrornamentioning
confidence: 71%